Ceroplastes ceriferus (Fabricius) (Hemiptera, Coccoidea): new pest of ornamentals in Europe? (Bollettino di zoologia agraria e bachicoltura, 2024)
The presence from Italian gardens of the wax scale Ceroplastes ceriferus (Fabricius) is reported. The species was found in North Italy on several ornamental species and appears to be already established. It is the first record of this species from outdoors in Europe. Ceroplastes ceriferus is probably native to Asia and is presently widespread in many countries of the world where is reported as pest of ornamental plants. It is a polyphagous species, has one generation/year and overwinters as adult female.
Keywords: Wax Indian scale; Coccidae; Italy; Ornamental plants